Identifikasi Molekuler dan Posisi Filogenetik Ikan Sili (Mastacembelidae: Macrognathus) dari Sungai Brantas, Jawa Timur, berdasarkan DNA mitokondria Gen COI - Wahyu Endra Kusuma; Ifa Sufaichusan; Bela Fatma Hani Ayu Lestari; Yuni Widyawati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
The spiny eels (family Mastacembelidae) is a fish that naturally and widely distributed on Java Island, especially in the Brantas River of East Java. This fish has high economic value, as a source of protein for local people and has recently popular as an ornamental fish among hobbyists. To fulfill market needs, fishermen must catch the fish from nature, leading to a severe population decline. Basic scientific information regarding species identification and determining the phylogenetic position fish species including the spiny eels is very important in order to support aquaculture, domestication and maintain its sustainability in nature. Specimens of the spiny eels were collected from Brantas River basin, East Java, at two localities in Malang and Kediri. Mitochondrial DNA from the cytochrome c oxidase subunit I was then sequenced on several randomly selected specimens. Results of morphological and genetic analysis using BLASTn showed that the specimens under study could be confirmed as Macrognathus aculeatus. Phylogenetic analysis using the Bayesian Inference method showed that M. aculeatus in this study has the closest relative to M. arai from Bangladesh. The phylogenetic reconstruction showed that individuals of M. aculeatus from Malang and Kediri were clustered together with individuals from Mojokerto with very shallow molecular divergence, indicating that they possibly originated from the same population. The results of this study can be used as basic information to design effective management of domestication, aquaculture, and conservation in the future.